Ответы и объяснения

  • Участник Знаний
2013-07-03T20:36:19+04:00
  • kefa
  • главный мозг
2013-07-03T21:32:13+04:00

первое:

 

64x^4+1+16x^2-16x^2=64x^2+16x^2+1-16x^2= \\ = (8x^2+1)-(4x)^2=(8x^2+1-4x^2)(8x^2+4x+1)

воспользовался формулами:

1) \ a+b=b+a \\ 2) \ a^2+2ab+b^2=(a+b)^2 \\ 1) a^2-b^2=(a-b)(a+b)

 

 

 

 

второе:

 

4x^4+1=4x^4+4x^2+1-4x^2=(2x^2+1)^2-(2x)^2= \\ = (2x^2-2x+1)(2x^2+2x+1)

воспользовался формулами:

 

\rm \ ECLI \ \ a=b, TO \ \ a \pm c=b\pm c

 

и из преыдущего решения